2021
DOI: 10.1093/mnras/stab2580
|View full text |Cite
|
Sign up to set email alerts
|

Resolving local and global kinematic signatures of satellite mergers with billion particle simulations

Abstract: In this work we present two new ∼109 particle self-consistent simulations of the merger of a Sagittarius-like dwarf galaxy with a Milky Way-like disc galaxy. One model is a violent merger creating a thick disc, and a Gaia-Enceladus/Sausage like remnant. The other is a highly stable disc which we use to illustrate how the improved phase space resolution allows us to better examine the formation and evolution of structures that have been observed in small, local volumes in the Milky Way, such as the z − vz phase… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
59
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(77 citation statements)
references
References 80 publications
17
59
0
1
Order By: Relevance
“…They further show that the influence of self gravity slows the growth of the phase spiral. This result that can also be seen by comparing the phase spiral found by Bland-Hawthorn & Tepper-García (2021) with the one seen in the analytic models of Binney & Schönrich (2018) which winds up quickly (see also Hunt et al 2021).…”
Section: Galactic Seismologysupporting
confidence: 72%

The disturbed outer Milky Way disc

McMillan,
Petersson,
Tepper-Garcia
et al. 2022
Preprint
“…They further show that the influence of self gravity slows the growth of the phase spiral. This result that can also be seen by comparing the phase spiral found by Bland-Hawthorn & Tepper-García (2021) with the one seen in the analytic models of Binney & Schönrich (2018) which winds up quickly (see also Hunt et al 2021).…”
Section: Galactic Seismologysupporting
confidence: 72%

The disturbed outer Milky Way disc

McMillan,
Petersson,
Tepper-Garcia
et al. 2022
Preprint
“…That study suggested that the phase spiral is a phase mixing signature after a perturbation. Further modelling has confirmed that the phase spiral can be a consequence of the Sagittarius dwarf galaxy tidal interaction (Binney & Schönrich 2018;Laporte et al 2019;Li & Shen 2020;Bland-Hawthorn & Tepper-García 2021;Hunt et al 2021;Gandhi et al 2021;Widmark et al 2021). Indeed, the estimated time of the perturbation roughly coincides with some of the previous pericenters of Sagittarius, estimated to ★ E-mail: begona01@ucm.es be between 200 and 1000 Myr ago (Law & Majewski 2010;Purcell et al 2011;Vasiliev & Belokurov 2020).…”
Section: Introductionmentioning
confidence: 90%
“…by the authors is reproduced in state-of-the-art simulations of Milky-Way crossings by dwarf galaxies, but perturbations by the buckling bar and by arms also succeed in reproducing similar structures (see, e.g. Hunt et al 2021;Khoperskov et al 2019).…”
Section: Comparisons With Recent Results On Dust and Starsmentioning
confidence: 90%